FRI0297 A Quantitative Videocapillaroscopic Study about The Main Categories of The "Scleroderma Pattern" and Their Correlation with The Clinical Features of Systemic Sclerosis (SSC). (15th July 2016) - De Angelis, R.; Di Donato, E.; Grassi, W.
Abstract : Background: Many studies have been carried out in systemic sclerosis (SSc) in order to correlate the microvascular damage with the clinical features and/or organ involvement, most of them through qualitative assessment of the morphological abnormalities forming the so-called "scleroderma pattern" (SP). Quantitative studies about the SP are currently scarce, rarely addressing the relationship with the disease characteristics. Objectives: To evaluate in a series of SSc patients the association between the types and extent of the SP with the clinical features and the disease severity. Methods: Fifty-four patients (47 women and 7 men, mean age 59.5 years, median disease duration 13.0 years) consecutively enrolled, underwent nailfold videocapillaroscopy. For each patient, a total of 32 images were collected (4 images for the II, III, IV, V finger of both hands). All images were classified according to the following patterns: normal, non-specific, SP (with no reduction of the capillary density and with avascular areas). The patterns were correlated with such features as sex, age, disease duration, Raynaud's phenomenon and/or digital ulcers (DU). Moreover, skin, muscle, gastrointestinal, pulmonary, heart and renal involvement were considered. Statistical analysis was performed using MedCalc version 12.0 (MedCalc Software, Mariakerke, Belgium). Results: A total of 1728 images were analyzed and patients were divided into 4 subsets, on the basis of the extent of the SP. In subset 1 (6 patients, 11.2%) the extent was less than 25%, in subset 2 (5 patients, 9.2%) the extent was between 25–50%, in subset 3 (16 patients, 29.6%) between 50–75%, in subset 4 (27 patients, 50%) was more than 75%. Subsets 1 and 2 showed no significant relationship with any of the variables considered. Patients of subset 3 had a significant correlation with the presence of DU (p=0.007). The subset 4 showed a significant correlation with disease severity (p=0.03), history of DU (p=0.04) and the presence of DU (p≤0.0001). SP without reduction of the capillary density was correlated with the presence of lung fibrosis (p=0.04). The SP with avascular areas showed a significant relationship with disease severity (p=0.001), lung fibrosis (p=0.01), gastrointestinal involvement (p=0.01), skin involvement (p=0.03), history of DU (p=0.04), and DU (p=0.001). No association was found between patterns and disease duration. Conclusions: The correlation observed between the presence of DU and/or history of DU both with the extent of the SP and the avascular areas represent a relevant data, confirming the hypothesis of a strong relationship between the fingertip blood perfusion and the integrity of the nailfold microvasculature. Unexpectedly, lung fibrosis showed a significant association both with the SP without reduction in capillary density and with the avascular areas. This fact leads us to consider the possibility of the multifactorial nature of pulmonary involvement, not only determined by a reduced number of capillaries. The lack of correlation between type and extent of the scleroderma pattern with the disease duration supports the concept that the severity of microangiopathy is not a characteristic of the late stages of the SSc. References: De Angelis R, et al. A growing need for capillaroscopy in rheumatology. Arthritis Rheum 2009;61:405–10. Disclosure of Interest: None declared